Development Strategies for Cassava and Banana Chips Enterprises: Insights from Basil Chips Case Study - Nikita Kaia Kanefi; Rafi Aditya Permana (Young Journal of Social Sciences and Humanities, 2025)
This research provides a comprehensive analysis of the development strategies applied by “Keripik Selasih,” a traditional small-scale cassava and banana chip enterprise that has been operating since 1995 in North Sumatra, Indonesia. Using a qualitative case study approach supported by in-depth interviews, direct observation of production activities, and literature review, this study identifies several strategic factors that strengthen the business's continuity and competitive position. These include consistent quality control through the use of fresh raw materials, the owner's expertise in production timing, ongoing product innovation in response to shifting consumer preferences, and integrated marketing strategies that combine conventional distribution channels with digital-based promotions. Despite facing various challenges such as limited working capital, fluctuations in raw material availability caused by seasonal weather changes, and an increasingly competitive snack market, Keripik Selasih continues to demonstrate business resilience. The sustainability of the enterprise is strongly influenced by adaptive management practices, long-term consumer trust, and experience-based decision-making. This study contributes to the broader discourse on the sustainability of traditional food-based microenterprises in Indonesia and provides practical recommendations for similar MSMEs aiming to strengthen market presence and achieve long-term growth.